Approximation Properties of the de la Vallée-Poussin Method - Rukasov, V. I.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We present a survey of results concerning the approximation of classes of periodic functions by the de la Vallée-Poussin sums obtained by various authors in the 20th century.